2016
DOI: 10.1007/s11011-016-9923-x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of geographic distributions of haptoglobin alleles with prevalence of multiple sclerosis (MS) – a narrative literature review

Abstract: We have proposed that the myelin damage observed in multiple sclerosis (MS) may be partly mediated through the long-term release and degradation of extracellular hemoglobin (Hb) and the products of its oxidative degradation [Cellular and Molecular Life Sciences, 71, 1789-1798, 2014]. The protein haptoglobin (Hpt) binds extracellular Hb as a first line of defense, and can serve as a vascular antioxidant. Humans have two different Hpt alleles: Hpt1 and Hpt2, giving either homozygous Hpt1-1 or Hpt2-2 phenotypes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 191 publications
2
8
0
Order By: Relevance
“…Therefore, Hp and transferrin types were studied in schizophrenic patients and control subjects by several groups. In agreement with our results, it has been demonstrated that Hp system displays a significant departure from the Hardy-Weinberg equilibrium with an excess of heterozygotes among the schizophrenic patients [ 18 ]. Likewise, the distribution of Hp types in the schizophrenic patients was significantly different from that in the controls.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Therefore, Hp and transferrin types were studied in schizophrenic patients and control subjects by several groups. In agreement with our results, it has been demonstrated that Hp system displays a significant departure from the Hardy-Weinberg equilibrium with an excess of heterozygotes among the schizophrenic patients [ 18 ]. Likewise, the distribution of Hp types in the schizophrenic patients was significantly different from that in the controls.…”
Section: Discussionsupporting
confidence: 92%
“…The positive acute phase proteins (APPs) are schizophrenic related proteins, with the highly concordant results on four positive APPs. In contrast to these reports, a study in Chinese patients revealed no such association between Hp or transferrin polymorphisms and schizophrenia [ 18 , 21 ]. Moreover, no reliable differences in the distribution of Hp phenotypes were found between schizophrenic patients and healthy Russian persons [ 22 ].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Chronic hemolysis results in the presence of a large amount of free hemoglobin in the blood, which is linked to increased endothelial adhesion and nitric oxide (NO) depletion [ 6 , 7 ], leading to a decrease of its vasodilator, antithrombotic, and anti-inflammatory properties [ 8 , 9 ]. The first line of cleaning free hemoglobin in the blood is a protein called haptoglobin (Hp) [ 7 , 10 ], which binds directly to free hemoglobin to form a very stable complex haptoglobin-hemoglobin (Hp-Hb), eliminated by macrophages via phagocytosis [ 6 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…16 Conversely, in Chile only 15% have the Hp2-2 haplotype. 16,17 Advancing maternal age has been seen to be associated with a higher prevalence of the Hp2-2 genotype. 18 In multiethnic Singapore, the prevalence of the Hp2 allele is at 83% in Indians compared with 67% in Chinese.…”
Section: Introductionmentioning
confidence: 99%